Introduction to flat panel displays. - Lee, Jiun-Haw, ....-; Liu, David N., ....-; Wu, Shin-Tson, ....- (Chichester : Wiley, 2008)
Chapter 1: Introduction 1.1 Flat Panel displays 1.2 Emissive and non-emissive displays 1.3 Display specifications 1.4 Applications of flat panel displays References Chapter 2: Color Science and Engineering 2.1 Introduction 2.2 The Eye 2.3 Colorimetry 2.4 Produce and re-produce colors References Chapter 3: Thin Film Transistors 3.1 Introduction 3.2 Basic concepts of crystallized semiconductor materials 3.3 Disorder semiconductor 3.4 TFT characteristics 3.5 PM and AM driving schemes 3.6 Non-Si based TFTs References Chapter 4: Liquid Crystal Displays 4.1 Introduction 4.2 Transmissive TFT LCDs 4.3 Liquid Crystal Materials 4.4 Liquid Crystal Alignment 4.5 Homogeneous Cell 4.6 Twisted Nematic (TN) 4.7 In-Plane Switching (IPS) 4.8 Fringe Field Switching (FFS) 4.9 Vertical Alignment (VA) 4.10 Optically Compensated Bend (OCB) Cell 4.11 Transflective LCDs 4.12 Future Directions References Chapter 5: Plasma Display Panels 5.1 Introduction 5.2 Physics of gas discharge 5.3 PDP panels 5.4 Front plate techniques 5.5 Rear plate techniques 5.6 Assembly and aging techniques 5.7 System techniques References Chapter 6: Light-emitting Diodes 6.1 Introduction 6.2 Material systems 6.3 Diode characteristics 6.4 Light-emitting characteristics 6.5 Device fabrication 6.6 Applications References Chapter 7: Organic Light-emitting Devices 7.1 Introduction 7.2 Energy states in organic materials 7.3 Photophysical process 7.4 Carrier injection, transport and recombination 7.5 Structure, fabrication and characterization 7.6 Improvement of internal quantum efficiency 7.7 Improvement of extraction efficiency References Chapter 8: Field Emission Displays 8.1 Introduction 8.2 Physics of field emission 8.3 FED structure and display mechanism 8.4. Emitter 8.5 Panel process 8.6 Field emission array (FEA) plate techniques 8.7 Phosphor plate techniques 8.8 Assembly and aging techniques 8.9 System techniques